Implementation Of Corporate Culture And A Positive Work Environment To Improve Internship Quality Of PT. Tourezia Cakra Inspira - Juliadi Syahputra; Fereshti Nurdiana Dihan (International Journal of Business and Quality Research, 2024)
This research aims to analyze the application of company culture and a positive work environment in improving the performance of the internship program at PT. Tourezia Cakra Inspira. The research method used is descriptive qualitative, allowing the author to obtain data through direct observation and interviews with employees and interns. Data was collected from various sources, including in-depth interviews, direct observation, and company documents related to human resource development. The research results showed that there were several problems in implementing the internship program, such as seniority measures and excessive work pressure, which caused several intern students to resign. This research provides recommendations for improving company culture and work environment, including by holding mentorship programs, transparent two-way communication, rewarding achievements, and creating a comfortable and ergonomic work environment. It is hoped that this research contribution can help PT. Tourezia Cakra Inspira in developing more effective strategies to improve the quality and retention of internship programs, thereby contributing to overall company performance